Delayed allergic reaction from bupropion in a 27-year-old male with MDD: A case report and literature review - Ana Anghel, BSc (Psych); G. Lucy Wilkening, PharmD (American Association of Psychiatric Pharmacists, 2024)
Introduction Bupropion is an antidepressant approved for the treatment of major depressive disorder (MDD), seasonal affective disorder, and smoking cessation. Nausea, headache, tremor, and insomnia are well-known adverse effects of this medication. Less well-recognized adverse effects include delayed allergic reactions, which, in some cases, can appear 2 or more weeks after bupropion initiation. Case Report A 27-year-old male with recurrent MDD was referred for medication treatment at an outpatient mental health clinic and prescribed bupropion XL. On day 28 of treatment, he reported significant improvement in depressive symptoms and the development of itchiness and urticaria on his extremities and back. Bupropion was tapered over the course of 7 days, and he was given cetirizine 10 mg daily. He was transitioned to venlafaxine treatment and experienced complete resolution of hives and pruritus. Discussion Despite published reports on bupropion causing delayed hypersensitivity reactions, there remains limited clinical recognition of this side effect, and the risk of underrecognition may be greater when the onset of the reaction is more than 2 weeks after bupropion initiation. Conclusion Bupropion can cause delayed hypersensitivity reactions, including delayed pruritis and urticaria. The risk may be highest in males aged 17 to 40 years and those with a history of allergic reactions.